Konsep Deradikalisasi Pemahaman Al-Qur’an Nasaruddin Umar - Nurullah Nurullah; Taqwiya Taqwiya (TAFSE: Journal of Qur'anic Studies, 2021)
Understanding of the Qur'an is growing in various circles. Starting from an understanding that presents Islamic values to an understanding that damages the image of the Qur'an and Islam itself. Like several verses related to war, they are taken exclusively as well as subjectively and textually which results in the emergence of an understanding that these verses are legitimacy and advice to fight using violence. This understanding is often categorized as a radical understanding. The deradicalization of the understanding of the Qur'an is an attempt to shift a radical understanding into a more moderate one. This paper aims to determine the concept and implications of deradicalization of Nasaruddin Umar's understanding of the interpretation of verses with the theme of war. This qualitative literature research is carried out by analyzing data and documents related to the discussion theme. The results showed that Nasaruddin Umar directed the understanding and interpretation of the Qur'an through a contextual approach. The implications of the concept are to give birth to a special concept of war in the perspective of the Qur'an. The Qur'an does legitimize the existence of war, but the legitimacy of the war has certain legal indications. Pemahaman terhadap al-Qur`an semakin berkembang di berbagai kalangan. Mulai dari pemahaman yang mempresentasikan nilai-nilai keislaman hingga pemahaman yang merusak image al-Qur`an dan Islam sendiri. Seperti beberapa ayat yang terkait dengan peperangan, dipahami secara eksklusif maupun subjektif dan tekstual yang mengakibatkan munculnya pemahaman bahwa ayat-ayat tersebut sebagai legitimasi dan anjuran untuk berperang dengan menggunakan kekerasan. Pemahaman ini sering dikategorikan sebagai pemahaman yang radikal. Deradikalisasi pemahaman al-Qur`an merupakan upaya mengalihkan pemahaman yang radikal menjadi lebih moderat. Tulisan ini bertujuan untuk mengetahui konsep dan implikasi deradikalisasi pemahaman Nasaruddin Umar terhadap penafsiran ayat-ayat dengan tema peperangan. Kajian kepustakaan yang bersifat kualitatif ini dilakukan dengan menganalisa data dan dokumen yang terkait dengan tema bahasan. Hasil penelitian menunjukkan bahwa Nasaruddin Umar mengarahkan pemahaman dan interpretasi Alquran melalui pendekatan kontekstual. Implikasi dari konsep yang ditawarkan tersebut melahirkan konsep khusus mengenai peperangan dalam perspektif al-Qur’an. Al-Qur’an memang melegitimasi adanya peperangan akan tetapi tegitimasi terhadap peperangan tersebut memiliki indikasi hukum tertentu.